Characterisation of Pumice-Kaolin Refractory Bricks for High Temperature Industrial Applications - AUDU, James; SALAWU, Abdulraman A.; AREMU, Muriana R.; ALHAJI, Abdullahi A.; SIUS, Lawal S. (FUDMA Journal of Engineering and Technology, 2026)
Pumice and kaolin refractory products are known to have outstanding resistance to thermal shock and high strength. However, knowledge about their optimization for better performance and sustainability is still not widely known. The objective of this study is to formulation and characterization of pumice-kaolin refractory bricks for its performance and sustainable properties in harsh industries.  The refractory bricks were produced by mixing pumice (75-300 µm) and kaolin (150 µm) at ratios of 25:75, 50:50 and 75:25 and then fired at 1200 °C. Thermogravimetric Analysis (TGA), Differential Thermal Analysis (DTA), X-ray Fluorescence XRF analysis, Fourier-Transform Infrared spectroscopy (FTIR) were used to investigate the physico-mechanical, chemical and thermal properties of the samples. It was seen that alumina and silica were the major oxides with the porosity extent ranging from 24.2% to 71.4% which corresponds with the insulating refractory requirements. The highest porosity achieved was 75% pumice blend with excellent thermal shock resistance after repeated thermal cycles, flexural strength remained 87.56% retaining only 12.44% flexural strength loss. Each sample showed extremely high refractoriness, that is, the sample doesn't melt or deform even at 1200 °C, which satisfies the requirement of insulating bricks in industry. Based on these results, pumice-kaolin composites are considered as good raw materials for industry especially for ceramic applications as well as energy-intensive applications, due to their low cost and sustainability with good properties.
Keywords: Refractory materials, Pumice, Kaolin, Refractoriness, High temperature.